The influence of supervisors and differences in ownership on tax avoidance by Indonesian Insurance Companies - Cecilia Ancelin Feodora Anthony; Ferry Irawan (WIM Solusi Prima, 2026)
Taxes are an important instrument for the sustainability of the state because taxes finance more than 82% of state expenditure. However, there are still many companies that engage in tax avoidance practices to increase their profits. These legal practices, which exploit grey areas in tax legislation, cost the state around 2 billion. Tax avoidance factors can vary, some of which include the role of supervisors and owners who should be instrumental in curbing tax avoidance practices so as not to cause harm to either the company or the state. This study aims to determine the effect of institutional ownership, independent commissioners, and gender diversity on the board of directors on tax avoidance. The selected companies are insurance companies listed on the Indonesia Stock Exchange during the period of 2019 to 2024. To test this, a quantitative method was used with secondary data sources, derived from company annual reports, with a total of 96 observations using purposive sampling. Data analysis was conducted using panel data regression and t-tests using STATA v.17 software. The results showed that the moderating effect of profitability weakened the relationship between institutional ownership and tax avoidance, while institutional ownership, independent commissioners, gender diversity in the board of directors, and the role of profitability, as well as the relationship between independent commissioners and board gender diversity, did not affect tax avoidance in insurance companies listed on the IDX.